KARAKTERISTIK BRIKET ARANG SABUT KELAPA DENGAN CANGKANG KELAPA SAWIT - Lasron Pahala Tua Nainggolan; Noviar Harun; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Briquettes is solid fuels made from waste biomass by the carbonization method. Coconut coir and palm shell are biomass wastes that are not used optimally. Coconut coir and palm shell contain a lot of lignin and cellulose which can be used as an energy source in the form of charcoal briquettes. The aims of this research were to get the best ratio of charcoal from a mixture of coconut coir charcoal and palm shell charcoal in the manufacture of charcoal briquettes in accordance with the Indonesian National Standard. This research was conducted experimentally using Completely Randomized Design (CRD) which consist of five treatments and four replications. The treatments in this research include the ratio of coconut coir charcoal and palm shell charcoal 50:50, 60:40, 70:30, 80:20, and 90:10. Data were statistically analyzed using Analysis of Variance (ANOVA) and then continued with Duncan’s Multiple Range Test (DMRT) at 5% level. The result of the analysis showed that the ratio of coconut coir charcoal and palm shell has a significant effect on water content, fix carbon content, ash content, and has not significantly affected calorific value.The best treatment briquettes was (50:50) with water content 5.09%, volatile matter content 52.79%, ash content 7.07%, fixed carbon content 35.06% and calorific value of 4882.11 cal/g. Keywords: coconut coir, palm shell, briquettes